On-chip optical sensors - Elsayed, Mohamed (AUC Knowledge Fountain, 2018)
Adding more functionality to chips is an important trend in the advancement of technology. During the past couple of decades, integrated circuit developments have focused on keeping Moore's Law alive "More of Moore". Moore's law predicts the doubling of the number of transistors on an integrated circuit every year. My research objectives revolve around "More than Moore", where different functionalities are sought to be integrated on chip. Sensing in particular is becoming of paramount importance in a variety of applications. Booming healthcare costs can be reduced with early diagnosis, which requires improved sensitivity and lower cost. To halt global warming, environmental monitoring requires miniature gas sensors that are cheap enough to be deployed at mass scale. First, we explore a novel silicon waveguide platform that is expected to perform well as a sensor in comparison to the conventional 220 nm thick waveguide. 50 and 70 nm shallow silicon waveguides have the advantage of easier lithography than conventional 220 nm thick waveguides due to the large minimum feature size required of 1 Âµm. 1 Âµm wide waveguides in these shallow platforms are single mode. A multi-mode interference device is designed in this platform to function as the smallest MMI sensor, giving sensitivity of 427 nm / refractive index unit (RIU) at a length of 4 mm. The silicon photonic MMI sensor is based on detecting refractive index changes. Refractometric techniques such as the MMI sensor require surface functionalization to achieve selectivity or specificity. Spectroscopic methods, usually reserved for material characterization in a research setting, can be adapted for highly specific label-free sensing. Chapter 4 explores the use of a highly doped III-V semiconductor for on chip infrared spectroscopy. Finite element method and finite different time domain were both used to design a plasmonic slot waveguide for gas sensing. On chip lasers and detectors have been designed using InAs. While InAs is still considered more expensive than silicon, the electronics industry expects to start incorporating more materials in standard fabrication processes, including III-V semiconductors for their superior properties including mobility. Thus, experimental realization of this sensor is feasible. A drawback with infrared spectroscopy is that it is difficult to use with biological fluids. Chapter 5 explores the use of Raman spectroscopy as a sensing method. To adapt Raman spectroscopy for sensing, the most important task is to enhance the Raman signal. The way the Raman signal is generated means that the number of photons is generally very low and usually bulk material or concentrated fluids are used as samples. To measure low concentrations of a probe molecule, the probe molecule is placed on a surface enhanced Raman spectroscopy (SERS) substrate. A typical SERS substrate is composed of metal nanostructures for their surface plasmon resonance property, which causes a large amplification in the electric field in particular hot spots. By decorated silicon nanowires with silver nanoparticles, an enhancement factor of 1011 was realized and picomolar concentrations of pyridine were detected using Raman spectroscopy. In conclusion, this thesis provides new concepts and foundations in three directions that are all important for on chip optical sensing. First, silicon photonics is the technology of choice that is nearest to the market and a multi-mode interference sensor based on shallow silicon waveguides was designed. Further work can explore how to cascade such MMIs to increase sensitivity without sacrificing the free spectral range. Second, infrared plasmonics is a promising technology. Before semiconductor plasmonics, on chip devices operated in the visible or near IR and then microwave region of the electromagnetic spectrum. By using highly doped semiconductors, it is possible to bridge the gap and operate with mid-infrared wavelengths. The implications are highlighted by designing a waveguide platform that can be used for next generation on chip infrared spectroscopy. Third, Raman spectroscopy was exploited as a sensing technique by experimental realization of a SERS substrate using equipment-free fabrication methods.